Working on optical characterization setup (fun experience of working with lasers!) for cutting-edge nanophotonics technology : part 3 - Phua, Randy Zheng Xiang (Nanyang Technological University, 2021)
Chemical bond spectroscopy, trace gas sensing, and medical diagnostics are all applications that benefit from the mid-infrared (MIR) wavelength region (3-50 m). Silicon photonics, particularly at the near infrared (NIR) wavelength, have piqued researchers' interest over the last decade as a possible candidate for meeting the growing demand for high data transmission capacity in communication systems. Scaling up the dimensions of silicon-on-insulator (SOI)-based devices to expand the activity wavelength to the MIR range is attracting research attention because of the wide range of possible applications in lab-on-chip sensors, free space communications, and more. Silicon(Si) is a desirable material for the MIR since it has low loss over a large portion of the MIR. We can take advantage of well-developed fabrication techniques and CMOS compatibility when we use Si, which makes the realization of on-chip integrated MIR devices more practical. However, there are a few great filters to achieve this. To begin with, the on-chip MIR photonics platform is still in its infancy. Second, Si has a low light emitting efficiency by default. Since Ge's bandgap is smaller than Si's, Germanium (Ge) on Si has gotten a lot of attention. Strained Ge has recently gotten a lot of attention because of an unusual physical property that allows it to become a direct bandgap material with enough tensile strain (e.g., >4.6 percent uniaxial tensile strain), making it ideal for use in light detection devices like photodetectors. However, Ge can only absorb light up to 1600nm, and there are no Ge-based MIR detectors on the market right now. In this study, we try to open the possibility of measuring MIR light using Ge on Si. We conduct a photocurrent measurement analysis at 3000nm using a photodetector based on a Ge on Si chip. First, we will go through the basics of energy band gaps, direct and indirect band gaps, and the Ge band structure (Chapter 2). It will also cover the basics of photodetectors and photocurrent, as well as strain-engineering of Ge and how it transforms Ge into a direct bandgap. The third chapter examines the literature on silicon photonics for MIR applications, the history of strained germanium experiments, and the state-of-the-art achievements from various system demonstrations in various material platforms by various organizations. The photodetector based on Ge on Si that was used in this study will be introduced in Chapter 4. The fabrication process will be outlined in depth, as well as the idea behind it. The setup used to test the photocurrent by exposing a Ge on Si device to a MIR laser is discussed in Chapter 5. Explanations of each individual components will be shown there. The photocurrent measurements that were obtained using the set-up will be quantitatively analyzed in Chapter 6. Finally, in Chapter 7, we will come to a conclusion about the analysis and the difficulties we encountered.